Новый подвид хентуанской круглоголовки — Phrynocephalus rossikowi shammakowi ssp. n. (Reptilia, Sauna. Agamidae) из Центральных Каракумов - Щербак, Н.Н.; Голубев, М.Л. (Вестник зоологии, 1979)
The new subspecies Phrynocephalus rossikowi shammacovi from the central region of the Kara-Kum desert (the isolated population) is described. It differs from the nominative form by peculiarities of pholidosis and pattern.